Does Daily Physical Activity Differ Between Patients with Femoroacetabular Impingement Syndrome and Patients with Hip Dysplasia? A Cross-Sectional Study in 157 Patients and 60 Healthy Volunteers - Lisa C. U. Reimer; Signe Kierkegaard; Inger Mechlenburg; Julie S. Jacobsen (International Journal of Sports Physical Therapy)
# Background The clinical presentation of femoroacetabular impingement syndrome (FAIS) and acetabular hip dysplasia (HD) are similar. However, the groups seem to differ regarding physical activity (PA) and sport.